2005
DOI: 10.1037/1072-5245.12.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Balancing Work and Home: How Job and Home Demands Are Related to Burnout.

Abstract: The aim of the present study was to make a clear distinction between work and home domains in the explanation of burnout. First, a 3-factor structure of job and home demands was hypothesized, consisting of quantitative demands, emotional demands, and mental demands. Next, a model was tested that delineates how demands in both life domains are related to occupational burnout through workϪhome interference (WHI) and homeϪwork interference (HWI). In doing so, the partial mediating role of WHI and HWI was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
356
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(397 citation statements)
references
References 42 publications
29
356
0
12
Order By: Relevance
“…The literature supports the finding that burnout is associated with non-occupational factors such as personal and stressful life events (Dyrbye et al, 2006; Peeters et al, 2005; Schonfeld & Bianchi, 2016). Participants cited family demands, financial demands, and personal demands as themes contributing to the experience of life demands.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The literature supports the finding that burnout is associated with non-occupational factors such as personal and stressful life events (Dyrbye et al, 2006; Peeters et al, 2005; Schonfeld & Bianchi, 2016). Participants cited family demands, financial demands, and personal demands as themes contributing to the experience of life demands.…”
Section: Discussionsupporting
confidence: 70%
“…Dyrbye et al (2006) confirmed that despite the notion that burnout is mainly linked to work-related stress, a strong relationship also exists between personal life events and professional burnout—highlighting the importance of investigating both job and personal demands in creating a better understanding of burnout as experienced by employees. The impact of job demands on burnout has been explored by various researchers (e.g., Alarcon, 2011; Seidler et al, 2014), and typically include aspects such as work overload, emotional demands, mental demands, work–home interference, role ambiguity, role conflict, role stress, stressful events, and time pressure (Olivares-Faúndez, Gil-Monte, Mena, Jélvez-Wilke, & Figueiredo-Ferraz, 2014; Lee & Ashforth, 1996; Peeters, Montgomery, Bakker, & Schaufeli, 2005; Schaufeli, Bakker, & Van Rhenen, 2009). In investigating the impact of life demands on burnout, life events have been found to have an impact on burnout risk, e.g., divorce, personal illness, illness or death of a close family member, marriage, birth, and adoption of a child (Dybre et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Role conflict is defined as the incongruity of expectations associated with a role (Kahn, Wolfe, Quinn, Snoek & Rosenthal, 1964); this can also be experienced when a person is expected to behave in a way that violates their personal values (Brewer & Clippard, 2002). There are many studies that show a positive relationship between role conflict and burnout (Lepine, Podsakoff & Lepine, 2005;Lee & Ashforth, 1996;Peeters et al, 2005;Schaufeli, 2007). Role ambiguity is the degree to which clear information does not relate to the expectation associated with a role (Kahn et al, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have identified the demands of role as burnout antecedents (Kokkinos, 2007;Peeters, Montgomery, Bakker & Schaufeli, 2005), since both role conflict and role ambiguity have been positively associated with this occurrence (Collins, 2000;Papastylianou, Kaila & Polychronopoulos, 2009;Schaufeli, Bakker, Heijden & Prins, 2009;Tunc & Kutanis, 2009). Role conflict is defined as the incongruity of expectations associated with a role (Kahn, Wolfe, Quinn, Snoek & Rosenthal, 1964); this can also be experienced when a person is expected to behave in a way that violates their personal values (Brewer & Clippard, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…De même, plusieurs études montrent que la difficulté de trouver un équilibre entre la vie professionnelle et familiale se répercute négativement sur la santé physique et mentale des parents (Grywacz, 2000 ;Demerouti et Geurts, 2004 ;Van Rijswijk et al, 2004 ;Bellavia et Frone, 2005 ;Bianchi et al, 2005 ;Oomens et al, 2007). À titre d'exemple plus concrets, des chercheurs (dont Peeters et al, 2005 ; de même qu 'Innstrand et al, 2008) identifient un lien entre la combinaison des exigences familiales et professionnelles et l'épuisement professionnel. Les parents subissent donc les conséquences négatives de devoir combiner plusieurs rôles.…”
Section: La Ctf Dans La Littératureunclassified